Muslim Feminists` Reading of the Quran: A Juristic Analysis on Family Law Issues (Mazahib, 2018)
Muslim feminist movement represents an indigenous voice among the contemporary literature on women and family. Its main contention is that women in Muslim society are accorded less favourable treatment especially in terms of legal rights. To remedy the situation, feminist scholarship`s main argument is that there is a need for feminist-reading of the sacred texts so as to purge the juristic legacy of male-biased views and achieve justice and equality for Muslim women in contemporary families. One principal methodological framework for this idea to materialise is to embark on the re-reading of the Qur`an from the women`s perspective. In this context, this paper presents issue-based analysis of Amina Wadud`s reading of the relevant Qur`anic passages on family law matters and finds that in spite of its merits, its main handicap lies on its methodological flaws, both in terms of approach and outcome. Methodologically, it is regarded as selective and ultra-vires of Islamic methodology of legal reform. It terms of impact, it is suspected as being tainted with Western inspired assumptions of rights in terms of justice and equality between the genders. To overcome this impasse, the paper argues for a mediated holistic approach to harmonise relations between men and women in the family.  Keywords: Family law, gender equality, justice, Muslim feminist.